Comparison of the Efficiency of the Botulinum Toxin for the Treatment of Esotropia in Children with and without Neurological Disease and/or Prematurity. Issue 4 (1st October 2020) - Mangan, Mehmet Serhat; Basar, Emel
ABSTRACT: Objective: To compare the effect of botulinum toxin injection for the management of esotropia in patients with and without neurological disease and/or prematurity. Methods: A single-center, retrospective, nonrandomized controlled study was performed on botulinum toxin in 87 children divided into two groups: study group of esotropia in 56 children with neurological disease and/or prematurity and, control group of 31 healthy children with infantile esotropia. All patients were followed for at least 24 months after injection. Success was defined as motor alignment with 10 Δ of orthotropia after single bilateral botulinum injection. Results: Mean age at treatment was similar in both groups (15.5 vs 14.8 months; p = .555). Mean pretreatment deviation was similar in both groups (50.8 Δ vs 50 Δ ; p = .855). The success rate was better in the control group (61.2% vs 51.7%, p = .265) at 24 months after injection, but the change in the mean angle of deviation was not statistically significant between the groups at 12 and 24 months after injection ( p = .264 and p = .547, respectively). Multivariate regression analysis showed that pretreatment angle of deviation and presence of retinopathy of prematurity were significant predictors at 12 months after injection ( p = .0001 and p = .004, respectively), while pretreatment angle of deviation was found to be a predictor at 24 months after injection ( p = .0001). Conclusions: Decreased angle of deviation and absence of retinopathy of prematurity were associated with a better result. There was no difference in motor alignment of esotropia in children with and without neurological disease and/or prematurity. In these patients, botulinum injection may be used as an alternative to surgery.